Preparation And Characterisation Of Epoxy/Kenaf/Mwcnts Hybrid Composites - Mat Noor, Noraina Alia (2019)
This research is to prepare and characterize epoxy/kenaf single-composites and MWCNTs filled epoxy/kenaf multi-scale hybrid composites for the resulted mechanical, thermal, physical and morphological properties. The composites are prepared by using a high speed mechanical stirring process with curing by the solution casting technique. At the first phase of this research, the parameter interaction study and optimization between kenaf fibre content (-5.00 wt. %; +35.00 wt. %), stirring time (-10.00 minutes; +50.00 minutes) and stirring speed (-100 rpm; +700 rpm) for epoxy/kenaf composite system was established by using two-level full factorial design. A set of 23 fractional factorial design for three independent variables, with three replication at centre point and no blocks was used to yield a total of eleven (11) sets of experiments. The Design Expert 6.0.8 software was used to optimize the stirring parameters and kenaf filler loading towards the maximum tensile strength (TS) response. The optimum stirring conditions was optimized into stirring speed at 100 rpm, stirring time at 10 minutes and 5 wt. % of kenaf filler content, with the highest repeatabilityR2 value of ~99.9%. The stage two of this research had specifically focus on the effect of MWCNTs nanofiller weight percentages addition into the epoxy/kenaf composites at 0.00, 0.25, 0.50, 0.75, 1.00 and 3.00 wt. %.The addition of MWCNTs as second reinforcement phase in epoxy/kenaf composites could enhanced the interfacial adhesion and provided good synergistic effects toward the properties enhancement for the epoxy/kenaf/MWCNTs hybrid composites. The multi-scale hybrid composites with 1.00 wt. % of MWCNTs addition, shows outstanding mechanical properties improvement (tensile strength: +48.24% and tensile modulus: +44.59%) as compared than epoxy/kenaf composite (controlled sample).The experimental results were supported with thermal and dynamic analyses. Addition of 1.00 wt.% MWCNTs into epoxy/kenaf composite have shifted glass transition temperature (Tg) at 43.90°C from 41.90°C for epoxy/kenaf composite without MWCNTs. This indicates the role of MWCNTs in improving thermal stability of the hybrid composite. In overall, MWCNTs filled epoxy/kenaf multi-scale hybrid composite, prepared by using an optimized stirring conditions and kenaf fibre loadings was able to provide hybrid synergism between both fillers and the epoxy matrix. Hence, contributed to significant improvement in hybrid composite stiffening effect.